Challenges and Opportunities of Araling Panlipunan Secondary Teachers in Teaching World History Lessons - Richard R. Delos Reyes (Future Science / FSH-PH Publications, 2026)
This study investigated the challenges and opportunities faced by Araling Panlipunan (AP) teachers in teaching World History in Zone 4, Division of Zambales. This study used a descriptive quantitative design among 98 educators from three schools of Subic, Castillejos, and San Marcelino districts. The results of this study showed that teachers frequently struggle with limited instructional resources, reliance on traditional strategies, and restricted learning activities. In spite of these challenges, opportunities occurred through hands-on approaches, thematic instruction, and technology integration. Statistical analysis showed that there are no significant differences in the challenges and opportunities across demographic profiles, except for gender-based variations in learning activities. Findings showed moderate positive correlation between challenges and opportunities. This concludes that teachers adapt creatively in response to challenges. This study recommends targeted teachers professional development, an adequate resource allocation, and curriculum flexibility which aims to improve World History instruction.